Literary Tool Evaluation as a Way of Introducing Digital Humanities in University Courses. The “Distant Poetry” case - Martínez Cantón, Clara I.; Ruiz Fabo, Pablo (Didáctica. Lengua y Literatura, 2019)
Technologies, with their ubiquitous dimension, have presence in all disciplines and have changed the way of studying and researching in the humanities, with fields such as Digital Humanities whose relevance is undeniable. Nevertheless, Humanities degrees in Spanish universities do not always reflect this digital turn. This paper presents the results of a teaching innovation activity. Its goal was to improve the acquisition of poetic metrics and the acquisition of transversal contents related to technology and digitality in a Modern Languages (Spanish) degree. The activity combined the teaching of Spanish metrics and of the computational technologies used for its automatic analysis in Digital Humanities projects, trying to involve the students in university research. The activity consisted in webconferences with international experts, and a task where the students were asked to metrically annotate sonnets, knowing that their annotation would be used to test a system for automatic metrical analysis. Results were measured by two means: a satisfaction form filled by students, and their marks in the course. Results show a clear improvement for those students that joined the activity and a high satisfaction with the technological and digital contents that they learnt. Some issues, such as sample size or the need of more data to compare are discussed.